Maternal Characteristic Factors Associated with the Incidence of Neonatal Jaundice in Newborns at PKU Muhammadiyah Yogyakarta - Shelviana Agustin; Anjarwati; Sri Ratnaningsih (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2026)
Neonatal jaundice is a common health problem in newborns due to increased bilirubin levels in the blood and has the potential to cause serious complications such as kernicterus. Globally, approximately 60% of full-term infants and 80% of premature infants experience jaundice in the first week of life. In the Special Region of Yogyakarta, 329 cases of neonatal jaundice were recorded in 2024. In addition to infant factors, maternal characteristics are also considered to play a role in the incidence of neonatal jaundice. This study aims to determine the correlation between maternal age, parity, and education level with the incidence of neonatal jaundice at PKU Muhammadiyah Hospital, Yogyakarta. Methods: This quantitative study employed an observational analytical design and a cross-sectional approach. Data were obtained from newborn medical records, including maternal age, parity, education, and jaundice incidence. Analysis used univariate and bivariate analysis with Fisher's Exact Test. The results showed that physiological jaundice was more common in infants of mothers aged 20-35 years (57.6%) and highly educated (48.5%). Pathological jaundice was more common in infants of mothers of high-risk age (42.4%). There was a significant association between maternal age and the incidence of neonatal jaundice (p = 0.006). However, there was no association between education level (p = 0.491) or parity (p = 0.363) and the incidence of neonatal jaundice. It is recommended that further research include other variables and increase the sample size for more comprehensive and accurate results.